Ligand-exchange processes on solvated zinc cations: Water exchange on [Zn(H2O)4(L)]2+·2H2O (L = Heterocyclic Ligand) - Alzoubi, Basam; Puchta, Ralph; van Eldik, Rudi (Chemistry - A European Journal, 2010)
The water-exchange mechanisms of [Zn(H2O)4(L) 2+·2H2O (L=imidazole, pyrazole, 1, 2, 4-triazole, pyridine, 4-cyanopyridine, 4-aminopyridine, 2-azaphosphole, 2-azafuran, 2-azathiophene, and 2-azaselenophene) have been investigated by DFT calculations (RB3LYP/6-311 + G**). The results support limiting associative reaction pathways that involve the formation of six-coordinate intermediates [Zn(H2O)5(L)]2+·H2O. The basicity of the coordinated heterocyclic ligands shows a good correlation with the activation barriers, structural parameters, and stability of the transition and intermediate states. © 2010 Wiley-VCH. Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Density functional calculations; Exchange interactions; Reaction mechanisms; Water chemistry; Zinc